Prevalence of Physical Activity in the United States: Behavioral Risk Factor Surveillance System, 2001 - Barbara E. Ainsworth, PhD, MPH; Harold W. Kohl III, PhD; C. Dexter Kimsey, PhD, MSEH; Caroline A. Macera, PhD; Sandra A. Ham, MS; Michelle M. Yore, MSPH; Deborah A. Jones, PhD (Centers for Disease Control and Prevention, 2005)
Introduction The health benefits of regular cardiovascular exercise are well-known. Such exercise, however, has traditionally been defined as vigorous physical activity, such as jogging, swimming, or aerobic dance. Exercise of moderate intensity also promotes health, and many U.S. adults may be experiencing the health benefits of exercise through lifestyle activities of moderate intensity, such as yard work, housework, or walking for transportation. Until recently, public health surveillance systems have not included assessments of this type of physical activity, focusing on exercise of vigorous intensity. We used an enhanced surveillance tool to describe the prevalence and amount of both moderate-intensity and vigorous-intensity physical activity among U.S. adults. Methods We analyzed data from the 2001 Behavioral Risk Factor Surveillance System, a state-based, random-digitdialed telephone survey administered to U.S. adults aged 18 years and older (n = 82,834 men and 120,286 women). Physical activity behavior was assessed using questions designed to quantify the frequency of participation in moderate- or vigorous-intensity physical activities performed during leisure time or for household chores and transportation. Results Overall, 45% of adults (48% of men and 43% of women) were active at recommended levels during nonworking hours (at least 30 minutes five or more days per week in moderate-intensity activities, equivalent to brisk walking, or at least 20 minutes three or more days per week in vigorous activities, equivalent to running, heavy yard work, or aerobic dance). Less than 16% of adults (15% of men and 17% of women) reported no moderate or vigorous activity in a usual week. Conclusion Integrating surveillance of lifestyle activities into national systems is possible, and doing so may provide a more accurate representation of the prevalence of recommended levels of physical activity. These results, however, suggest that the majority of U.S. adults are not active at levels associated with the promotion and maintenance of health.